Strategi Bisnis dalam Meningkatkan Citra Produk Buket Balon di Sosial Media - Nur Fitri Wulandari; Tri Khoiril Ikhlakh; Rahma Sabrina; Gunawan Aji (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The use of social media as a product sales and marketing platform is growing and becoming a trend in today's digital era. In the midst of increasingly fierce business competition, Buket Balon as a manufacturer of decoration products that uses social media as a marketing and sales tool, is required to continue to innovate and improve product image so that it remains in demand by consumers. Therefore this study aims to analyze and find out the factors of how business strategy can improve the image of the Buket Balon product on social media and provide recommendations for Buket Balon to increase sales and profits through social media. This research uses a qualitative-descriptive approach, using the case study method. The informants of this study are consumers of Bouquett balloons. The results of this study Researchers analyzed that Business Strategy in Improving the Image of Balloon Bouquet Products on Social Media Occurs due to several factors, namely promotion, content, discount techniques and copywriting. These factors were apparently influenced by internal and external informants. Suggestions from researchers for SMEs that when making strategies to improve product image can pay attention to these aspects. It is inseparable that now everything is digital-based, so we have to prove that MSMEs are also not left behind